New development: IPSAS adoption, from G20 countries to village governments in developing countries. Issue 2 (17th February 2020) - Fahmid, Imam Mujahidin; Harun, Harun; Graham, Peter; Carter, David; Suhab, Sultan; An, Yi; Zheng, Xiaosong; Fahmid, Mirah Midadan
ABSTRACT: This article discusses the latest developments in IPSAS adoption by the G20 states and beyond, the expected outcomes of IPSAS adoption in the public sector, and the experiences of a south east Asian economy (Indonesia) in using an IPSAS-based reporting system at the village level. The potential limitations of IPSAS, especially in less developed countries, are addressed. The authors make recommendations for policy-makers about successfully adopting IPSAS in emerging economies. IMPACT: The authors explain why international agencies, like the World Bank, must fully consult with central and local government officials and other stakeholders in developing countries to ensure that the introduction of developed countries' reporting systems, like IPSAS, are redesigned in accordance with the capacities and needs of recipient countries.